Transcatheter mitral valve replacement versus redo surgery for mitral prosthesis failure: A systematic review and meta-analysis - Zhou, Jiawei; Li, Yuehuan; Chen, Zhang; Zhang, Haibo (Frontiers in Cardiovascular Medicine, 2023)
Background Transcatheter mitral valve replacement (TMVR) has emerged as an alternative to redo surgery. TMVR compared with redo surgical mitral valve replacement (SMVR) in patients with mitral prosthesis failure remains limited. In this study, we performed a meta-analysis to assess the outcomes of TMVR (including valve-in-valve and valve-in-ring) versus redo surgery for mitral prosthesis failure. Methods We comprehensively searched the PubMed, Embase, and Cochrane library databases according to predetermined inclusion and exclusion criteria, and then we extracted data. We compared the outcomes of TMVR and redo SMVR for mitral prosthesis failure in terms of the in-hospital mortality, stroke, renal dysfunction, vascular complication, pacemaker implantation, exploration for bleeding, paravalvular leak, mean mitral valve gradient, 30-day mortality, and 1-year mortality. Results Nine retrospective cohort studies and a total of 3,038 patients were included in this analysis. Compared with redo SMVR for mitral prosthesis failure, TMVR was associated with lower in-hospital mortality [odds ratios (OR): 0.44; 95% confidence interval (CI): 0.30–0.64; P < 0.001], stroke (OR: 0.44; 95% CI: 0.29–0.67; P = 0.0001), renal dysfunction (OR: 0.52; 95% CI: 0.37–0.75; P = 0.0003), vascular complication (OR: 0.58; 95% CI: 0.43–0.78; P = 0.004), pacemaker implantation (OR: 0.23; 95% CI: 0.15–0.36; P < 0.00001), and exploration for bleeding (OR: 0.24; 95% CI: 0.06–0.96; P = 0.04). Conversely, redo SMVR had lower paravalvular leak (OR: 22.12; 95% CI: 2.81–174.16; P = 0.003). There was no difference in mean mitral valve gradient (MD: 0.04; 95% CI: −0.47 to 0.55; P = 0.87), 30-day mortality (OR: 0.65; 95% CI: 0.36–1.17; P = 0.15), and 1-year mortality (OR: 0.96; 95% CI: 0.63–1.45; P = 0.84). Conclusion In patients with mitral prosthesis failure, TMVR is associated with lower in-hospital mortality and lower occurrence of postoperative complications, except for paravalvular leak. TMVR offers a viable alternative to the conventional redo surgery in selected patients.